2012
DOI: 10.1080/10410236.2011.606526
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Daughter Communication About Sex: The Influence of Authoritative Parenting Style

Abstract: Parent-child communication about sex has been shown to delay sexual activity and increase contraceptive and condom use. The influence of authoritative parenting style and mothers' perception of daughters' risk on communication about sex was examined in this study. Mothers in a random sample (n=283) with daughters aged 9-15 years were mailed surveys asking about communication with their daughters regarding 11 sex-related topics. Multivariate linear regression was used to assess the influence of authoritative pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 41 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…Current age of the daughter predicted timing of first discussions about sex (Askelson, Campo, & Smith, 2012; Miller et al, 2009b), and sex communication occurs earlier with daughters than with sons (Beckett et al, 2010). Parents are less likely to talk with younger teens about sex (Swain et al, 2006), and they reported discussions to be more challenging with younger rather than older daughters (Coffelt, 2010).…”
Section: Personmentioning
confidence: 99%
“…Current age of the daughter predicted timing of first discussions about sex (Askelson, Campo, & Smith, 2012; Miller et al, 2009b), and sex communication occurs earlier with daughters than with sons (Beckett et al, 2010). Parents are less likely to talk with younger teens about sex (Swain et al, 2006), and they reported discussions to be more challenging with younger rather than older daughters (Coffelt, 2010).…”
Section: Personmentioning
confidence: 99%
“…As reported in different studies, parent-child communication about sexuality had a positive effect on delaying sex debut or increasing safer sex practice through condom use (Askelson, Campo, & Smith, 2012) and reducing high-risk behaviors (McBride et al, 2007;Sutton, Lasswell, Lanier, & Miller, 2013). While in China, as similar to many other countries, most parents do not communicate with their children on sexual issues (Romo, Lefkowitz, Sigman, & Au, 2002), especially in rural areas where discussion of sex is considered taboo.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies focused on several specific topics, such as contraception, family planning, and abortion to explore participants' perspectives using qualitative approaches, mainly in Western countries (Akers et al , ; Sisco et al , ). Other studies applied surveys to describe factors associated with communication about specific sexual topics, such as abstinence, puberty, reproduction, birth, STI, dating and relationships (Wilson & Koo, ; Askelson et al , ).…”
Section: Literature Reviewmentioning
confidence: 99%